Hospitality students' work experiences and an examination of their perceptions of the future. Issue 2 (2nd April 2016) - Schoffstall, Donald G.; Arendt, Susan W.
ABSTRACT: The purpose of this study was to compare perceptions of work experience while in college between hospitality students and hospitality graduates and to examine differences among their work experiences and perceptions of a professional future. Senior level students and graduates from hospitality programs across the United States participated in the study. Study results showed that 50% of current hospitality students work 21 or more hours per week, while more than 10% worked 40 or more hours per week; both students and graduates perceive their work experiences positively. Both students and graduates rated work experience highest in importance when interviewing for industry jobs.